Analysis of the Influence of Fault Fracture Zone on Mining Response Based on FDM-DEM Coupling. (21st June 2022) - Xu, Cao; Xiaoshan, Cao; Tielin, Han; Yan, Ru
Abstract : Fault slip will cause a change in mining stress at the longwall face, which will cause adverse effects. In this study, on the basis of Fast Lagrangian Analysis of Continua in 3 Dimensions (FLAC3D) and Particle Flow Code in 3 Dimensions (PFC3D), the sliding of the fault fracture zone and its impact on the longwall working face were analyzed. The rock mass of the fault fracture zone with a certain thickness was constructed using rigid random model particles. The coupling between the wall element of PFC3D and the zone element of the continuous medium in the software was used to realize the transmission of force and displacement, and the interaction between the fault fracture zone and the working face was studied. The influence of the slip of different fault zone positions on the fault and working face was also explored using the method of externally disturbing the fracture zone of the fault. The numerical results showed that as the distance between the fault and the working face continued to decrease, the peak stress concentration in front of the longwall face first increased, then decreased, and gradually shifted to the vicinity of the fault zone. The stress mutation and fault slip occurred within a certain distance of the longwall face from the fault. When fault slip activation begins, the stress near the fault zone showed a sudden change of varying degrees with the advancement of the longwall face. This sudden change was caused by the influence of mining activities from the activation distance of the rock in the fault fracture zone and the rolling extrusion of the rock mass in the fracture zone. When the fault zone closer to the working face was disturbed, the influence on the fault zone and longwall face was greater. When the fault zone near the coal seam was disturbed, the rock mass and working face near the fault zone brought different degrees of dynamic responses, which were mostly instantaneous and had high frequency and amplitude. The results of this research could help in the mining of longwall mining affected by fault zones and have a certain guiding role in coal mining before crossing faults.